(untitled) (Bangladesh Journal of Zoology, 2019)
To assess the abundance of black tiger shrimp (Penaeus monodon) post larvae (PL) and to quantify the damage of different aquatic fauna during collection of shrimp PL. About 37 PL of other shrimps, 11 fin fish larvae and 31 macrozooplankton were wasted during collection of a single shrimp PL. During the survey period, around 1.55 million man days/year were estimated to be involved in shrimp PL collection activities and on average 216 million of shrimp PL were collected annually from the studied area. About 17,064 million of other shrimps, fin fishes and macrozooplankton were destroyed annually by shrimp seed collectors in Kuakata beach. Variation in water surface temperature and pH was not found but salinity and hardness showed great fluctuation during the study period. Water temperature, salinity and pH are significantly (p<0.01) correlated with shrimp PL abundance. Therefore, the results imply that present seed collection practice causes severe damage of other valuable aquatic fauna, which directly affect the faunal diversity, natural productivity and self recruitment pattern of mother stock. Bangladesh J. Zool. 47(2): 273-283, 2019